Website Utilization of Indonesian Learning Material as a Media for Disabled Students in Creating Scientific Works - Cahyo Hasanudin; Ayu Fitrianingsih; Muhamad Sholehhudin; Nabila Ulfaida (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2024)
The learning material website of Indonesian language contained materials of Indonesian language course. This website was very useful for students as additional learning material. Therefore, this study aimed to investigate the components of website as Indonesian learning materials. This study was literature study with primary and secondary data sources. Result of study showed that website of Indonesian language contained the access of main menu, material menu, and media menu. It could be concluded that website of Indonesian language could be utilized as learning media for disabled students in compiling scientific works.